A realidade aumentada como ferramenta de promoção de vendas - Marcelo Torronteguy Valle (2020)
This research addresses the use of augmented reality content as a part of the point of sale promotion strategy. The main research question is to determine whether the use of an application with augmented reality can facilitate the visualization and localization of the promotions available at the physical point of sale and, consequently, influence the shopping experience. To answer this question, an application was created with augmented reality content, so that it can measure the influence that this technology can have on the perception of promotions within stores. Strategic points in the aisles of a supermarket will receive an augmented reality marker. By pointing the device at those locations, the user will be able to view highlighted, with augmented reality, the promotional content related to the products. In this research, two homogeneous groups will be analyzed. The first group will receive the experimental condition, that is, will use the augmented reality application developed for this project, while the second group will serve as a control and will go through the supermarket aisles and view the products without receiving this stimulus. Statistical analysis of questionnaires applied to participating consumers will allow to identify possible behavioral differences between groups. Finally, questionnaires will also be used, exclusively with the experimental group, to assess the usability of the developed application.